Fenomena Sosial Masyarakat Sekitar Kawasan Konservasi: Studi Kasus Masyarakat Penyangga Kawasan Taman Wisata Alam (TWA) Sorong Provinsi Papua Barat - Mutiono, Mutiono (JPAP: Jurnal Penelitian Administrasi Publik, 2020)
The success of managing forest resources in Indonesia that it has not been massive yet, the track record of the progression has shown due to mindset of managing forest that tend to antisocial. Conservation area of Sorong Nature Recreation Park (TWA Sorong) can't be separated from its community and culture. This study aims to uncover social phenomenom of the people in TWA Sorong as the implication of community interaction with surrounding forest resources. This research based on constructivism paradigm with qualitative approach. The strategy used is case study strategy trough observation method, interview and desk study. The results shows in its historical development, TWA Sorong has asymmetric information phenomena betwen government and the community that can direct its status to an illegitimate legal condition. The community arround the area are more of the type of oral tradition and tend to post-truth so that in interpreting the objective truth of the law that tend to appear simplification of law phenomena. In the cultural context, there is shifting of culture phenomena which shows a shift in the meaning of customary rights which were originaly interpreted as rights that have religio-magical ties but nowdays it's interpreted more economically.